Language, Dialect, and Power in the Film Capharnaum (2018): A Sociolinguistic Perspective - Fikri, Muhamad Yusuf (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
The film Capernaum (2018) has been widely analyzed as a social critique of poverty, child exploitation, and the state’s failure to protect marginalized groups. However, studies that specifically highlight linguistic practices in this film remain limited, particularly in examining how language functions within power relations. This study aims to analyze how language is used to shape and represent power relations among characters in the film Capharnaum (2018) using Michel Foucault’s theory of power relations. This study employs a sociolinguistic approach with qualitative descriptive methods and discourse analysis techniques applied to character dialogues, particularly in institutional scenes such as courtrooms and everyday interactions within marginalized communities. The research data consists of character utterances that reflect linguistic practices in various social contexts. The expected results will demonstrate that language in the film Capharnaum functions as a discursive practice that shapes and represents power relations among characters. Power is not solely held by specific individuals but is exercised through the use of language in social interactions. Characters in positions of authority tend to use language to direct and control the course of interactions, particularly within institutional spaces. Conversely, marginalized characters are in a constrained position, yet in certain situations are able to use language as a form of resistance. Thus, language functions not only as a tool for communication but also as a medium that reflects and produces power relations within the social structure.